Czy polskie firmy realizują założenia marketingu personalnego? Wyniki badań empirycznych - Baruk, Agnieszka (Do Polish Firms Realize Principles of Personnel Marketing? - Results of Empirical Research, 2006)
In the paper the problems of realizing personnel marketing by Polish firms were presented. On the base of results of field researches the authoress described the main disfunctions in staff activities which caused negative consequences for researched organizations. Conducted researches pointed оut that in mentioned firms personnel marketing was not implemented and its role was not understood.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 218-226